The effect of nostalgia on the travel decisions of older tourists to visit socially sustainable tourist destinations - Ian Patterson; Adela Balderas-Cejudo (Journal of Humanities and Applied Social Sciences)
Purpose – This paper sets out to answer the following research question: Is nostalgia an important travel motive that helps to explain why older tourists choose a specific sustainable destination? Design/methodology/approach – This paper is a conceptual paper and uses a systematic literature review as the main method of secondary data analysis. Findings – The findings suggest that nostalgia significantly contributes to the overall tourism experience, because older travelers often have a strong sense of nostalgia that dominates their memories and provides a positive view of the past that contributes to a greater sense of continuity and meaning in their lives. Research limitations – Being a conceptual paper is its limitation in itself. For DMOs and marketers, it is important to understand what are the specific characteristics of a sustainable destination that are likely to serve as a cue for developing nostalgic emotions to help promote it. This can be achieved by designing nostalgic advertisements that are based on the history and cultural uniqueness of tourist attractions that stimulates the older tourists' love of history and culture, to motivate them to visit these sustainable destinations. DMOs need to capitalize on the nostalgic sentiments that are expressed by older tourists themselves that should also be used to promote nostalgia as a marketing strategy to attract potential consumers. To achieve this, potential tourists need to be shown imagery of older adults living their lives to the fullest. These include sharing photos of seniors doing “soft adventure” activities such as kayaking, hiking, and camping as well as other social activities such as dancing, socializing, learning, and cooking as examples of all the activities that older adults used to do when they were younger. Another strategy is for DMOs to use virtual reality trips to demonstrate that nostalgia contributes to sustainable tourism as it can accurately portray a destination’s atmosphere and to include its rich sensorial appeal. Nostalgia that is evoked by virtual reality has also been found to facilitate the marketing of “slow travel”, which encourages experiences of deep cultural exploration which entails choosing slower transportation, thus highlighting environmental consciousness (Juhl and Biskas, 2023). Future studies are needed to investigate how the beneficial effects of nostalgia can be employed to improve the quality of people’s social lives through sustainable tourist experiences. Practical implications – For DMOs and marketers, it is important to understand what are the specific characteristics of a sustainable destination that are likely to serve as a cue for developing nostalgic emotions to help promote it. This can be achieved by designing nostalgic advertisements that are based on the history and cultural uniqueness of tourist attractions that stimulates the older tourists' love of history and culture, to motivate them to visit these sustainable destinations. DMOs need to capitalize on the nostalgic sentiments that are expressed by older tourists themselves that should also be used to promote nostalgia as a marketing strategy to attract potential consumers. To achieve this, potential tourists need to be shown imagery of older adults living their lives to the fullest. Another strategy is for DMOs to use virtual reality trips to demonstrate that nostalgia contributes to sustainable tourism as it can accurately portray a destination’s atmosphere and to include its rich sensorial appeal. Social implications – Raising awareness of ageism and the need to market older individuals in a different way is key. Originality/value – Nostalgia is related to sustainable tourism, especially to the pillar of social sustainability that helps to bring people together. It is also regarded as one of the main contributing motives behind an older traveler’s choice of a sustainable destination. However, very few studies have acknowledged the importance of nostalgia as a motivation for travel, especially for repeat visitations.